2017
DOI: 10.1155/2017/2045382
|View full text |Cite
|
Sign up to set email alerts
|

Drug Errors and Protocol for Prevention among Anaesthetists in Nigeria

Abstract: Background Drugs are often prescribed, dispensed, and administered by the same person during anaesthesia, and this may increase the risk of drug error. Objectives To assess the frequency of drug administration errors by anaesthetists, the drugs commonly involved, and the effects of such errors. Method A questionnaire-based study was carried out among participants at an annual conference of Nigerian anaesthetists. Sixty-six of the 80 participants returned the completed questionnaire. The respondents comprised 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Several survey studies had reported the occurrence rate of anesthetic medication errors. [ 19 , 20 , 23 , 36 ] The occurrence was high and ranged from 70 to 95%. Nanji et al[ 1 ] conducted a prospective observational study to assess medication errors and adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several survey studies had reported the occurrence rate of anesthetic medication errors. [ 19 , 20 , 23 , 36 ] The occurrence was high and ranged from 70 to 95%. Nanji et al[ 1 ] conducted a prospective observational study to assess medication errors and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies presented similar results: Double-checking before withdrawing and administering medication was the most effective drug safety measure. [ 20 , 21 , 23 ] McCawley et al[ 18 ] found that in 84.4% of reported errors, a second clinician was unavailable to double-check. However, the two-person confirmation is limited, owing to difficulty ensuring the availability of a second clinician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation